The Role of Magnetic Resonance Imaging and Ultrasonography in the Early Detection of Psoriatic Arthritis Lesions - Kryś, Zuzanna; Mirkowski, Karol; Michalik, Zuzanna (Journal of Education, Health and Sport, 2026)
Psoriatic arthritis (PsA) is a chronic immune-mediated musculoskeletal disease associated with psoriasis and characterized by heterogeneous involvement of peripheral joints, entheses, tendon sheaths, nails and the axial skeleton. Because early PsA may be oligosymptomatic or clinically silent, diagnostic delay remains a major challenge and may lead to irreversible structural damage. This narrative review summarizes the role of magnetic resonance imaging (MRI) and ultrasonography (US) in the early detection, assessment and monitoring of PsA-related lesions. Ultrasonography is a widely accessible, dynamic and cost-effective imaging modality that enables real-time assessment of synovitis, tenosynovitis, enthesitis, dactylitis, nail-unit abnormalities and vascular activity using Power Doppler. It is particularly useful in peripheral disease and may help identify subclinical inflammation in patients with psoriasis. MRI provides superior visualization of deeper inflammatory lesions, including bone marrow edema, osteitis, sacroiliitis, axial involvement, synovitis, and soft-tissue inflammation. It is especially valuable when conventional radiography is normal or when axial or bone marrow involvement is suspected. Both modalities support earlier diagnosis, monitoring of disease activity, and evaluation of treatment response, particularly in the context of biologic therapy and treat-to-target strategies. However, their interpretation requires clinical context. MRI is limited by cost, availability, and examination time, whereas ultrasound remains operator- and equipment-dependent. Subclinical lesions may also be nonspecific and do not always predict progression to clinically manifest PsA. Overall, MRI and ultrasonography should be regarded as complementary tools that may improve early detection, guide personalized treatment decisions, and reduce the risk of irreversible joint damage in patients with psoriatic disease.